Globalization. The integration process and change in the legal profession - Cáceres Valdez, Rudy (2021)
The legal profession is in the process of adapting to a globalized world that is increasingly international. This globalization of law goes hand in hand with the internationalization of the economy and politics. The answer is the internationalization of law. Today we can see how legal matters, clients, conflict, court, knowledge, institutional life and therefore internationalize the occupation. All this leads us to the lawyer should know integration processes occurring mainly for economic reasons such as the European Union and the Andean Community of Nations, but these processes have also led to the internal rules are changed based on the decisions of international tribunals, in this context, counsel should handle international law and how we engage national law these decisions at the supranational level. To achieve this goal the professional law must handle not only theoretical knowledge, you must also know the vast practical field for a better proposal in resolving conflicts. It is transcendent know how to manage the new reality and is here where the role lawyers play becomes crucial because they embody and compensate the lack of an institutional structure, ie that the lawyer has increasingly become a representative office of the company. The recent development of international mediation and arbitration are a clear example of the new trend. In conclusion the internationalization of law is our profession adapting to globalization.